Association between Charlson comorbidity index and survival outcomes in patients with prostate cancer: A meta-analysis - Feilun Cui; Yue Qiu; Wei Xu; Yong Shan; Chunlin Liu; Chen Zou; Yu Fan (Heliyon, 2024)
Objective: This meta-analysis aimed to assess the influence of comorbidity, as assessed by the Charlson comorbidity index (CCI), on survival outcomes in patients with prostate cancer (PCa). Methods: We conducted a comprehensive search of the PubMed, Web of Science, and Embase databases to identify studies that examined the association between CCI-defined comorbidity and survival outcomes in PCa patients. We employed a random effect model to merge adjusted hazard ratios (HR) with 95 % confidence intervals (CI) for survival outcomes. Results: Sixteen studies reporting on 17 articles, which collectively included 457,256 patients. For the presence (CCI score ≥1) versus absence (CCI score of 0) of comorbidity, the pooled HR was 1.59 (95 % CI 1.43–1.77) for all-cause mortality, 0.98 (95 % CI 0.90–1.08) for PCa-specific mortality, and 1.88 (95 % CI 1.61–2.21) for other-cause mortality. When compared to a CCI score of 0, the pooled HR of all-cause mortality was 1.30 (95 % CI 1.18–1.44) for a CCI score of 1, 1.65 (95 % CI 1.37–2.00) for a CCI score ≥2, and 1.75 (95 % CI 1.57–1.95) for a CCI score ≥3. Additionally, the pooled HR of other cause mortality was 1.53 (95 % CI 1.41–1.67) for a CCI score of 1, 1.93 (95 % CI 1.74–2.75) for a CCI score ≥2, and 3.95 (95 % CI 2.13–7.34) for a CCI score ≥3. Conclusions: Increased comorbidity, as assessed by the CCI, significantly predicts all-cause and other-cause mortality in patients with PCa, but not PCa-specific mortality. The risk of all-cause and other-cause mortality increases with the burden of comorbidity.